Norbornene/n‐Butyl methacrylate copolymerization over α‐Diimine nickel and palladium catalysts supported on multiwalled carbon nanotubes. Issue 22 (8th September 2014) - Huo, Ping; Liu, Wanyun; He, Xiaohui; Chen, Yiwang
ABSTRACT The covalently immobilized multiwalled carbon nanotubes (MWNTs) supported three‐dimensional geometry α‐diimine nickel, palladium catalysts are prepared by corresponding α‐diimine nickel, palladium complexes and activated MWNTs. The molecular structures of the catalysts have been confirmed by X‐ray single‐crystal analyses, NMR and XPS, as well as elemental analysis. Compared with nickel, palladium catalysts without modification and physical mixing of nickel, palladium catalysts with MWNTs, the MWNTs supported nickel, palladium catalysts show improved activity and productivity in norbornene homopolymerization and copolymerization with polar monomer. The morphology of the resulting polymers obtained from MWNTs‐supported nickel(II) complex reveals that the MWNTs are dispersed uniformly in polymer and wrapped by polymers to squeeze out of spherical particles, leading to the enhanced processability and mechanical properties. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3213–3220